Numerical studies for small-scale solar chimney power plants with various geometric configurations - Saadun, Mohd Noor Asril; Che Sidik, Nor Azwadi; Xian, Teng Meng; Mohd Rosli, Mohd Afzanizam (2023)
With annual increases in energy demand, solar chimney power plants (SCPP) are regarded as one of the renewable energy power plants. It can potentially be an alternative renewable energy source such as photovoltaic (PV) cells and wind when properly developed. This study primarily focuses on determining the optimal size of a SCPP by examining various geometrical characteristics of the SCPP. The approach for this investigation included utilizing Computational Fluid Dynamics (CFD) to simulate the flow within the SCPP. Three essential parameters were examined in this investigation: the chimney’s height, its diameter, and the shape of the SCPP’s solar collector. The model was developed using 3D visualization tools, and the results were validated to demonstrate that it fulfils the degree needed for the model’s intended purpose or application. In addition, the simulation was used to investigate the temperature and air velocity of the SCPP. It was discovered that increasing the chimney height, decreasing the diameter of the chimney, and utilising a square collector will help improving the SCPP’s performance. By expanding the chimney height, the temperature and air velocity will be higher, but the air velocity decreases after exceeding 4.0 m of chimney height. The optimal diameter shows at 16 cm when both temperature and air velocity are at their maximum values. In contrast, the air velocity generated by the square collector is more than the air velocity produced by the circular collector. In order to improve simulation results, it is recommended to cross-reference with experimental data specifically.